The factors of package tours from umrah travel agency on customer selection in Segamat, Johor / Muhammad Izzuddin Halim Roja - Halim Roja, Muhammad Izzuddin (Faculty of Business and Management, 2019)
Umrah is voluntary act and can be performed anytime in order to encourage good fortune toward the Muslim around the world. Only exception for Umrah is during the days of Hajj. Currently in Malaysia, do Umrah is like more to seek the practical for the Hajj, and cause the demand of making umrah. Where the umrah travel agencies must operate under Tourism Industry Act 1992 also with the Lesen Khas Umrah (LKU). Therefore, this paper aims to recognize the factors of customer selection on the umrah travel agencies in the Segamat, Johor. The dependent variable is customer selection. This is to identify the choices of package tours from umrah travel agencies on customer selection in Segamat. The independent variable is service quality, hotel & airlines, time, routing & tour program, word-of-mouth and price. This research will present primary data collected from the potential customers in Segamat which 100 questionnaire will be distribute to the respondent also the online questionnaire with distributed by convenience sampling method. The methodology that be used is the descriptive analysis, reliability and validity test and regression analysis will be conducted SPSS 22 package. This research will be expected same with the previous research, where the package tours that provide the service quality is the highest among the factors in the analysis because of the quality, its reputation and service quality of the travel agencies itself and the lowest is routing & tour program. After this research have been conducted, the outcome shows the highest factors package tours is the price and also service quality and the lowest is same with the previous research were routine and tour program is the lowest.